Facilities management : User's satisfaction on facilities at Sport Centre in UiTM Shah Alam / Mohamad Farid Ridhwan Mad Rosip - Mad Rosip, Mohamad Farid Ridhwan (Faculty of Architecture, Planning and Surveying, 2015)
The facilities management is an important role to sustain or maintain the facilities at every sector. Facilities management not just be placed under building, but it also cover road, road lighting, park and etc. The facilities management also get involved in the management of sport centre. The aim of facilities management at sport centre is to help and maintain the facilities at sport centre where sport centre management did not have specialities in certain cases. For this study, UiTM Shah Alam Sport centre had been chosen as a case study. The reason why UiTM Shah Alam Sport Centre was chosen because, this institution has their own management team to handle all kind of problems. The objective of this study is to understand on how facilities management as carried out by UiTM Facility Management and Sport Centre Management. Other than that, it also to know or gain the level of satisfaction of the user regarding to the facilities management at sport centre. This objective will be achieved by the distribution of questionnaire and will be analyse to gain the result. After all the data had been analysed, the follow up recommendation will be given to the problems. From general view, the facilities management at sport centre is composition of planning, organizing and controlling the function ability of the facilities at sport centre. It also monitors the introduction of new technologies or new method in facilities management.